A Documentation Proposal for Manuscripts in Libraries A Case Study: İstanbul University Faculty of Letters Rare Books Library - Kuzucuoğlu, Alpaslan H.; Kiraz, M.Nilüfer; Ünsalan, Ozan; Taşdemir, İbrahim (Information World, 2015)
Libraries are important institutions which transferred unique cultural heritage from past to present. The role of conservation works is essential in transmitting of the books, manuscripts and documents which reflect near past to the next generations in a healthy way. Bringing into the ideal levels of indoor comfort (climatic) conditions is one of the protection studies in the library environments. Temperature, relative humidity, light, radiation, dust, vibration; microbiological activity, biological factors: insects and rodents, intentional / unintentional acts of human-induced factors and disaster factors affect library buildings and collections. The collections which have their vulnerable chemical structure nature are faced with a very quick deterioration or extinction. Due to the all of these reasons, necessary precautions should be taken by measurement, assessment and continuous monitoring of the library materials for indoor environment before any kind of deterioration. In this study, proposal of solution based on Geographic Information Systems (GIS) and Raman Spectroscopic Analysis, which provides fast data analysis for the diagnosis of deterioration occurring over time, has been proposed. It is aimed that deterioration in the manuscripts in the libraries depending on the ambient conditions, by using digital and optical imaging such as Raman Spectroscopy method, GIS and to collect a database of these records for the future studies. Using of data obtained from this study as base in the diagnosis and restoration works and as tool in development of conservation policies are emphasized. Spectroscopic analysis were performed by Raman spectroscopic techniques. According to the Raman spectroscopy results, it was determined that pigments were used for manuscripts. On the other hand, deterioration levels were defined by GIS with high precision.